Kewajiban Menjaga Kerahasiaan Dalam Pembuatan Akta Bagi Calon Notaris Magang - Anggun Ludy Hardani (Officium Notarium, 2021)
There are two formulations of the problem in this study: first, what are the obligations of prospective notary apprentices in a notary office? Second, how can the sanctions for violating Article 16 of Law Number 2 of 2014 on Notary Positions be applied to prospective notary apprentices? This study uses a normative juridical approach. By reviewing a statutory regulation as a basis for solving problems. Research data were collected by interviewing notaries and prospective notaries who had carried out their internship obligations, as well as reviewing laws and regulations, books and other documents related to research. The results of this research are that the obligations of prospective notary apprentices have been well-stated in the law; and prospective notary apprentices who violate the obligation to keep the deed a secret cannot be equated with sanctions imposed on notaries.Keywords: Deed; obligation; prospective notary; secretAbstrakTerdapat dua rumusan masalah dalam penelitian ini: pertama, apakah kewajiban calon notaris magang di kantor notaris? Kedua, bagaimana sanksi terhadap pelanggaran Pasal 16 Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris dapat diterapkan pada calon notaris magang? Penelitian ini menggunakan pendekatan yuridis normatif. Dengan mengkaji suatu peraturan perundang-undangan sebagai dasar dalam melakukan pemecahan masalah. Data penelitian dikumpulkan dengan cara wawancara kepada notaris dan calon notaris yang telah melaksanakan kewajiban magang, serta mengkaji peraturan undang-undangan, buku pustaka maupun dokumen lainnya yang berkaitan dengan penelitian. Hasil dari penelitian ini bahwa kewajiban calon notaris magang adalah apa yang ada dalam undang-undang. Calon notaris magang yang melanggar kewajiban merahasiakan akta tidak dapat dipersamakan dengan sanksi yang dikenakan kepada notarisKata Kunci: Akta; calon notaris; kerahasiaan; kewajiban